2019
DOI: 10.3390/nano9091275
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Nanomaterials

Abstract: Nanomaterials possess stunning physical and chemical properties [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Over the past few years, researchers have shown interest in green chemistry to synthesize NPs using environmentally benign agents such as plants, fruits, flowers, algae, yeasts, bacteria, fungi. Additionally, extensive research has been carried out using plant extracts for the synthesis of NPs, and it was observed that compared to other means, plants are more suitable for the production of NPs, even at the pilot scale [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, researchers have shown interest in green chemistry to synthesize NPs using environmentally benign agents such as plants, fruits, flowers, algae, yeasts, bacteria, fungi. Additionally, extensive research has been carried out using plant extracts for the synthesis of NPs, and it was observed that compared to other means, plants are more suitable for the production of NPs, even at the pilot scale [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the production stage, the twelve principles of green chemistry provide a suitable framework for manufacturing NPs and NP-enabled technologies. These principles are intended to guide the design of chemical routes that yield enhanced sustainability outcomes (Gilbertson et al, 2015 ; Benelli, 2019 ). Nevertheless, the fact that NPs can be produced through sustainable approaches does not mean that the fabricated NPs are intrinsically safe and that their use and release in the environment will not cause harm.…”
Section: Sustainability Considerations and Concluding Remarksmentioning
confidence: 99%
“…Green synthesis of nanomaterial means avoiding using hazardous chemicals that toxic the products while synthesis the nanomaterial or nanoparticle. So, the green methods are considered as a friendly technique to synthesize nanoparticles appropriate for the environment and human health 1,2,3 . Although other common methods can produce large quantities of nanoparticles with the required morphology and size, the production -cost is high, and consumed toxic substances 4,5 .…”
Section: Introductionmentioning
confidence: 99%